Do weight loss and adherence cluster within behavioral treatment groups?. (2nd December 2013) - Wing, Rena R.; Leahey, Tricia; Jeffery, Robert; Johnson, Karen C.; Hill, James O.; Coday, Mace; Espeland, Mark A.; ,
<x xml:space="preserve">Abstract</x> Objective Weight loss programs are often conducted in a group format, but it is unclear whether weight losses or adherence cluster within treatment group and whether characteristics of the group (e.g., size or homogeneity) affect outcomes. We examined these questions within Look AHEAD, a multicenter study of the effects of an intensive lifestyle intervention (ILI) in overweight/obese individuals with type 2 diabetes. Methods Weight losses and adherence (attendance, use of meal replacement products, and minutes of activity) were examined over one year of intervention in 2329 ILI participants in 209 treatment groups, which all received the same weight loss program. Results Weight losses did not cluster among members of a treatment group (intra‐class correlation [ICC] of 0.007), whereas measures of adherence had small/moderate clustering (ICCs of 0.05‐0.11). The 209 groups varied in weight losses, with a mean of 8.64% (SD = 2.35%, interquartile range = 6.82%, 10.32%), but neither size nor baseline homogeneity of members affected the outcome. Conclusions Although these findings suggest that it may not be necessary to control for clustering in behavioral weight loss studies, they also indicate that merely treating individuals in groups is not sufficient to harness social influences on weight loss.